SISTEM MANAJEMEN PENDIDIKAN BERBASIS MOBILE (TREN APLIKASI MOBILE UNTUK GURU, ORANG TUA DAN SISWA) - Sarah Nur’aeni Khoiriyah; Irkham Auladi; Siswadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of information technology has driven significant transformations in educational management, one of which is through the implementation of the Mobile-Based Education Management System (MBEMS). This system allows teachers, students, and parents to access educational services via mobile devices. This study aims to describe trends in the use of mobile applications in educational management at a school that has implemented a digital system. The method used is a qualitative descriptive approach through observation, interviews, and documentation. The results show that at MA Ma'arif NU Sains Al-Qur'an Sumbang, teachers have utilized the e-Rapor application for grade processing, but learning outcome reporting has not been done online. Meanwhile, students use the digital library as a medium for literacy and independent learning. Communication between the school and parents is still conducted through the WhatsApp Group application, which serves as a means of conveying academic information, attendance, and announcements of school activities. Although not yet integrated into a single mobile-based management system, the implementation of this technology demonstrates a positive trend towards more efficient, transparent, and participatory educational management.